2013
DOI: 10.1007/s12308-013-0182-z
|View full text |Cite
|
Sign up to set email alerts
|

Enteropathy-associated anaplastic large T cell lymphoma ALK-positive (EA-ALCL-ALK+): variant of T cell lymphoma with possible two-hit pathogenesis

Abstract: Enteropathy-associated T cell lymphoma (EATL) and anaplastic large T cell lymphoma ALK-positive (ALCL-ALK+) are two well-defined and recognized T cell lymphoma entities. We report a case of primary ileal lymphoma in a 68-year-old male with a well-established long-standing his

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Due to the aforementioned clinical and histological findings unusual for EATL, notably, the prolonged clinical course of the disease, the possibility of a less aggressive process, such as indolent T‐cell lymphoproliferative disorder of the GI tract was considered in our case. The CD4‐/ CD8+ immunoprofile was in keeping with this possibility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the aforementioned clinical and histological findings unusual for EATL, notably, the prolonged clinical course of the disease, the possibility of a less aggressive process, such as indolent T‐cell lymphoproliferative disorder of the GI tract was considered in our case. The CD4‐/ CD8+ immunoprofile was in keeping with this possibility.…”
Section: Discussionmentioning
confidence: 99%
“…These typically occur in patients with chronic inflammatory or autoimmune disorders, and follow indolent course over several years. More recently, one of our authors reported an unusual case of an aggressive enteropathy‐associated ALCL, diagnosed in a 68‐year‐old male with a well‐established long‐standing history of celiac disease, where the patient died of disease within 3 months after the initial diagnosis was made . This case was thought to represent a T‐cell lymphoma variant with two‐hit pathogenesis, since it combined features specific to two distinct lymphoma types, including the typical clinical presentation and histopathologic aspects of EATL, and the CD30 expression, and evidence of ALK‐gene rearrangement (ALK‐gr), by both immunohistochemistry (IHC) and fluorescence in situ hybridization (FISH), which are virtually diagnostic of ALCL.…”
mentioning
confidence: 99%